PERANCANGAN UI/UX APLIKASI MOBILE PANGAUBAN KARINDING DENGAN MENGGUNAKAN FIGMA - Lubis, Novitasari Ramadhani; Anggraini, Novita; Senubekti, Mamok Andri (LPPM Universitas Putera Batam, 2025)
This study aims to design the User Interface (UI) and User Experience (UX) of the Pangauban Karinding mobile application as a medium for preserving the art and education of traditional Sundanese musical instruments. Pangauban Karinding functions as a digital space that documents, archives, and shares the dynamics of perkarinding strategically and sustainably. Although this platform is already available in the form of a website, the development of a mobile version was carried out to increase accessibility and user engagement, especially among the younger generation who are more familiar with mobile devices. The method used is a prototyping approach with the help of the Figma application, which supports the process of making wireframes, interface design, and testing interactive prototypes. The application design is carried out through the stages of analyzing user needs, creating navigation and display structures, and evaluating functionality through user feedback. The final results show that the proposed UI/UX design is able to provide a more structured, informative, and attractive user experience than the previous platform. With this application, the preservation of the Karinding culture is not only packaged in an educational way, but also adaptive to the development of technology and the digital behavior of today's society.